Pengetahuan, Sikap, Preferensi dan Perilaku Konsumsi Teh Gaharu di KPHP Unit XXIII Sarmi - Kende, Henoch; Moeljono, Soetjipto; Hendri, Hendri (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: This study aimed to examine the knowledge, attitudes, preferences, and consumption patterns of agarwood tea in KPHP Unit XXIII Sarmi, Papua Province. This research was conducted in Tetom Jaya, Kiren, Bebon Jaya, and Srum, which cultivate agarwood. The sampling procedure for respondents is based on the Slovin formula and a structured questionnaire. The data were then analyzed using a Likert scale and the smart PLS-SEM statistical analysis in further detail. The level of community knowledge regarding the consumption of agarwood tea from both internal and external sources is enough (40-59,99%) - excellent (80-100%). Attitudes are included in the less (20-39,99%) – good (60-79,99%) categories, while preferences are included in the good (60-79,99%) category, and behavior is included in the insufficient (<40-59,99%) category. In addition, the PLS-SEM analysis indicates that T statistics are more significant than 1.96 and p-values are less than 0.05, indicating that exogenous latency variables from external, internal, and attitudes influence preferences, influencing the consumption of agarwood tea sachets.